2018
DOI: 10.1002/hrm.21897
|View full text |Cite
|
Sign up to set email alerts
|

The social context of compensation design: Social norms and the impact of equity incentives

Abstract: Drawing on arguments from institutional theory, this study examines how social norms—specifically, local religious social norms—affect the motivational impact of equity‐based incentives. We test our model using longitudinal data on local religious norms, CEO equity incentives, and firm value. Consistent with our theoretical predictions, we find that local religious social norms attenuate the impact of CEO option incentives upon firm value. Furthermore, we find that the attenuating impact of local religious soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 143 publications
(333 reference statements)
0
4
0
Order By: Relevance
“…In this regard, research is needed on how diversity policy and related norms influence relationships among members with different religious (or nonreligious) identities and subsequent individual, work group, and organizational effects. We note that Zolotoy, O'Sullivan, and Martin (2018) have found that religion-based social norms affect the motivational impact of using equity-based incentives. We infer that religion can play a heretofore unrecognized role in differential responses at the individual and group-level to organizational practices and policies.…”
Section: Adopting a Multilevel Approachmentioning
confidence: 75%
“…In this regard, research is needed on how diversity policy and related norms influence relationships among members with different religious (or nonreligious) identities and subsequent individual, work group, and organizational effects. We note that Zolotoy, O'Sullivan, and Martin (2018) have found that religion-based social norms affect the motivational impact of using equity-based incentives. We infer that religion can play a heretofore unrecognized role in differential responses at the individual and group-level to organizational practices and policies.…”
Section: Adopting a Multilevel Approachmentioning
confidence: 75%
“…Most of the previous studies on the mechanisms of religion and corporate governance have concluded that religion improves by reducing the agency costs between shareholders and management (Du et al, 2013), inhibiting the behavior of major shareholders who hollow out listed companies (Du et al, 2014), curbing overinvestment (Du Xingqiang et al, 2016), and reducing the risk of stock price crashes (Zeng Aimin and Wei Zhihua, 2017). Some scholars also focus on specific forms of corporate governance, arguing that the stronger the religious atmosphere, the more stable the board structure (Chintrakarn et al, 2016), and that CEO option incentives are associated with reduced sensitivity to firm value (Zolotoy et al, 2018). a study by Shen and Su (2017) found that having religious beliefs especially family business founders with oriental religious beliefs tend to pass down the actual control of the business to the next generation.…”
Section: Religious Climatementioning
confidence: 99%
“…Source: Organized by the author Considering the endogeneity of economic relationships, i.e., religious climate can inhibit managers' self-interested and short-sighted behaviors, which can have a positive effect on firms' ESG performances; at the same time, when firms have good ESG performances, managers are more inclined to use a long-term oriented decision-making perspective and are able to take stakeholders into account, which makes managers more willing to locate their firms in areas with a strong religious climate in order to facilitate the establishment of a relevant corporate culture. Therefore, in order to address the possible endogeneity issue, this paper adopts the instrumental variable method and propensity matching score method to test the results of this paper with reference to the study by Jiang, Aihua (2023) [11]. Specifically, this paper constructs the following instrumental variables: adopting terrain data of each region as the instrumental variable terrain data as the instrumental variable satisfies (1) exogeneity: terrain data is exogenous and has no direct correlation with the ESG performance of enterprises.…”
Section: The Impact Of Buddhism and Taoism On Corporate Esg Performancementioning
confidence: 99%
“…BAM can also accommodate the notion of gains and losses in moral utility for decision-makers, and how they affect various stakeholders. For instance, satisfying the community's desire for a clean environment through pollution control (Berrone et al, 2010), local social norms (Zolotoy et al, 2018), and shareholders' desire to avoid wealth loss (Martin et al, 2019).…”
Section: Research On Managerial Decisions From a Bam Perspectivementioning
confidence: 99%